GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 186995 species occurrences available in GBIF matching the query: TaxonKey: Poa supina Schrad. or Trifolium arvense L. or Rubus spectabilis Pursh or Vaccinium oxycoccos L. or Brassica elongata Ehrh. or Trifolium montanum L. or Fragaria viridis Duchesne or Avena fatua L. or Diplotaxis tenuifolia (L.) DC. or Ribes nigrum L. or Corylus avellana L. or Vicia sativa L. or Lactuca sibirica (L.) Benth. ex Maxim. or Daucus carota L. or Rubus chamaemorus L. or Humulus lupulus L. or Festuca rubra L. or Rorippa islandica (Oeder) Borbás or Beta vulgaris L. or Malus sylvestris Mill. or Rubus laciniatus (Weston) Willd. or Ribes uva-crispa L. or Poa pratensis L. or Armoracia rusticana P. Gaertn., B. Mey. & Scherb. or Trifolium repens L. or Erucastrum gallicum (Willd.) O.E. Schulz or Barbarea stricta Andrz. ex Besser or Trifolium pratense L. or Juglans regia L. or Prunus domestica L. or Setaria viridis (L.) P.Beauv. or Allium fistulosum L. or Vaccinium uliginosum L. or Brassica rapa L. or Fragaria ×ananassa (Weston) Decne. & Naudin or Dactylis glomerata L. or Trifolium hybridum L. or Prunus cerasus L. or Ribes rubrum L. or Fragaria moschata Duchesne or Phleum pratense L. or Allium schoenoprasum L. or Barbarea vulgaris (L.) W.T. Aiton or Lolium multiflorum Lam. or Prunus avium (L.) L. or Sinapis arvensis L. or Poa palustris L. or Crambe maritima L. or Lolium perenne L. or Prunus spinosa L. or Trifolium medium L. or Diplotaxis muralis Hegetschw. or Rubus caesius L. or Vicia lathyroides L. or Poa alpina S.Watson or Malus domestica Borkh. or Rubus arcticus L. or Fragaria vesca L. or Lactuca serriola L. or Medicago lupulina L. or Medicago sativa L. or Vicia villosa Roth or Festuca ovina L. or Brassica nigra (L.) W.D.J. Koch or Poa trivialis L. or Prunus mahaleb L. or Prunus cerasifera Ehrh. or Vaccinium vitis-idaea L. or Cichorium intybus L. convar. radicosum (Alef.) J.Holub or Asparagus officinalis L. or Vaccinium myrtillus L. or Rubus armeniacus Focke or Rubus allegheniensis Porter or Vaccinium microcarpum (Turcz. ex Rupr.) Schmalh. ex Busch or Carum carvi L. or Pyrus communis L. or Ribes spicatum E. Robson or Rubus idaeus L. or Festuca brevipila R.Tracey Country: Norway HasCoordinate: true Year: >= 1970. The dataset includes 186995 records from 49 constituent datasets: 2 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from Phanerogamic Botanical Collections (S). 6825 records from Jordal. 3 records from Lindesnes. 10755 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 2 records from Naturalis Biodiversity Center (NL) - Botany. 1981 records from Species plots from the Norwegian Vegetation Mapping Programme. 7042 records from BioFokus. 4 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 2640 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 26 records from Artdata. 1227 records from Stabbetorp - Floristiske registreringer 2016. 2203 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 9 records from OHN. 470 records from Norwegian Biodiversity Information Centre - Other datasets. 416 records from Vascular Plant Herbarium, UiB. 5 records from iNaturalist Research-grade Observations. 198 records from ARKO strandeng. 31 records from HUCS - Herbário da Universidade de Caxias do Sul. 2851 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 4 records from NMNH occurrence DwC-A. 33 records from naturgucker. 1 records from Red list project inventory, vascular plants. 1 records from Rådgivende Biologer. 2 records from svalbardflora.net. 1 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Herbarium Berolinense. 1 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 176 records from Nordic Genetic Resources. 11829 records from Vascular Plants, Observations, Oslo (O). 2 records from Polish gene bank – passport data of plants accessions which are important in human life. 13 records from E39 Lyngdal - Ålgård. 83 records from Vascular Herbarium, NMBU. 94 records from Faun. 16 records from Lund Botanical Museum (LD). 73534 records from Norwegian Species Observation Service. 215 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 317 records from Fremmede arter - spredningsvegen «import av planteprodukter». 1 records from Botany (UPS). 18 records from Verneplan Hjerkinn karplanter. 317 records from Kartlegging av dragehode. 2528 records from Tromsø Museum, Vascular plants. 1923 records from Vascular Plant Herbarium, Trondheim (TRH). 34948 records from Vascular Plants, Field notes, Oslo (O). 378 records from Ecofact. 38 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 7954 records from Vascular Plant Herbarium, Oslo (O). 135 records from SWECO. 15742 records from Vascular Plants, Field notes, Trondheim (TRH).
Keywords: GBIF; biodiversity; species occurrences